Discharge sensitivity of collapsible drip tapes to water temperature - Ana C. S. de Araujo; José A. Frizzone; Antonio P. de Camargo; Diego J. de S. Pereira; Verônica G. M. L. de Melo; Wagner W. A. Bombardelli (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective of this study was to quantify the effect of water temperature variations on the discharge of collapsible thin-walled drip tapes with integrated non-pressure-compensating emitters. The tests were conducted in the laboratory using an automated test bench. Tests were performed to determine the discharge-pressure curves by varying the water temperature from 20 to 50 °C. Nine emitter models of three wall thicknesses (6, 8, and 9 MIL) were evaluated. The coefficients K and x of the discharge-pressure curves varied according to the water temperature. In flat emitters of turbulent flow (x < 0.5), the discharge decreased as the temperature increased. In the welded emitters of turbulent flow, several responses were observed. Regarding emitter D (x > 0.5), the discharge increased as the temperature was increased, while for emitter C (x < 0.5), the discharge decreased; the highest discharge variations occurred at pressures higher than 60 kPa. For embossed emitters, the discharge increased as a function of temperature, however, the greatest variation occurred at the lowest pressures. None of the emitters showed significant difference in the discharge variation due to wall thicknesses.